Effect of nitrogen on cellular production and release of the neurotoxin anatoxin-a in a nitrogen-fixing cyanobacterium - Gagnon, Alexis; Pick, Frances R. (Université d'Ottawa | University of Ottawa, 2012)
Anatoxin-a (ANTX) is a neurotoxin produced by several freshwater cyanobacteria and implicated in lethal poisonings of domesticated animals and wildlife. The factors leading to its production in nature and in culture are not well understood. Resource availability may influence its cellular production as suggested by the carbon-nutrient hypothesis, which links the amount of secondary metabolites produced by plants or microbes to the relative abundance of nutrients. We tested the effects of nitrogen supply (as 1, 5, and 100% N of standard cyanobacterial medium corresponding to 15, 75, and 1500 mg L−1 of NaNO3 respectively) on ANTX production and release in a toxic strain of the planktonic cyanobacterium Aphanizomenon issatschenkoi (Nostocales). We hypothesized that nitrogen deficiency might constrain the production of ANTX. However, the total concentration and more significantly the cellular content of anatoxin-a peaked (max. 146 μg/L and 1683 μg g−1 dry weight) at intermediate levels of nitrogen supply when N-deficiency was evident based on phycocyanin to chlorophyll a and carbon to nitrogen ratios. The results suggest that the cellular production of anatoxin-a may be stimulated by moderate nitrogen stress. Maximal cellular contents of other cyanotoxins have recently been reported under severe stress conditions in another Nostocales species.
Keywords: cyanobacteria; anatoxin-a; nitrogen deficiency; carbon-nutrient hypothesis